Photocatalytical Degradation of Methyl Orange using laboratory prepared Copper Oxide photocatalyst - Rajbhandari Nyachhyon, Armila; Neupane, Gobinda (Scientific World, 2024)
Copper oxide materials have been successfully synthesized by the chemical precipitation method using copper nitrate, sodium hydroxide and sodium lauryl sulphate. As prepared materials were characterized by using XRD and FTIR. The XRD data reveals that as prepared CuO is crystalline in nature. The particle size of the material was found to be approximately 10 nm indicating nano-sized particle. Photocatalytic efficiency of CuO nanoparticle was then studied. In this study, methyl orange (MO) was used as model dye pollutant. The MO degradation rate using CuO photocatalyst was studied at different pH condition, varying time of UV irradiation, variation of catalyst dose. Results revealed that the optimum pH was found to be 3 and optimum time was found to be 150 min using optimum dose of 0.05g under UV light irradiation in presence of H2O2 in MO dye solution. The rate constant of MO degradation was found to be 0.0099 min-1 indicating good rate of reaction which was in agreement with literature value 0.0089 min-1.